Compromised Cortical-Hippocampal Network Function From Transient Hypertension: Linking Mid-Life Hypertension to Late Life Dementia Risk - Lai, Aaron Y.; Bazzigaluppi, Paolo; Morrone, Christopher D.; Hill, Mary E.; Stefanovic, Bojana; McLaurin, JoAnne (Frontiers in Neuroscience, 2022)
Mid-life hypertension is a major risk factor for developing dementia later in life. While anti-hypertensive drugs restore normotension, dementia risk remains above baseline suggesting that brain damage sustained during transient hypertension is irreversible. The current study characterized a rat model of transient hypertension with an extended period of normotensive recovery: F344 rats were treated with L-NG-Nitroarginine methyl ester (L-NAME) for one month to induce hypertension then allowed up to four months of recovery. With respect to cognitive deficits, comparison between one month and four months of recovery identified initial deficits in spatial memory that resolved by four months post-hypertension; contrastingly, loss of cognitive flexibility did not. The specific cells and brain regions underlying these cognitive deficits were investigated. Irreversible structural damage to the brain was observed in both the prefrontal cortex and the hippocampus, with decreased blood vessel density, myelin and neuronal loss. We then measured theta-gamma phase amplitude coupling as a readout for network function, a potential link between the observed cognitive and pathological deficits. Four months after hypertension, we detected decreased theta-gamma phase amplitude coupling within each brain region and a concurrent increase in baseline connectivity between the two regions reflecting an attempt to maintain function that may account for the improvement in spatial memory. Our results demonstrate that connectivity between prefrontal cortex and hippocampus is a vulnerable network affected by transient hypertension which is not rescued over time; thus demonstrating for the first time a mechanistic link between the long-term effects of transient hypertension and dementia risk.